Ab initio study of structural, electronic and elastic properties of CdSe1−xSx semiconductor. (December 2017) - Zafar, Muhammad; Shakil, M.; Ahmed, Shabbir; Raza-ur-rehman Hashmi, Muhammad; Choudhary, M.A.; Naeem-ur-Rehman,
Highlights: Structural, electronic and elastic properties of CdSe1−x S semiconductor alloy are calculated. All theoretical calculations are performed using Quantum ESPRESSO with LDA pseudo potential. LDA+U method was used to enhance the band gap up to experimental value. CdSe1−x S semiconductor alloy is ductile for full range of concentration. Abstract: In this work plane wave pseudo-potential method was used to study the structural, electronic, and elastic properties of zinc-blende CdSe1−x Sx semiconductor alloys using local density approximation (LDA). The ground-state properties are resolute for the bulk materials CdS, CdSe, and their alloys. Very small deviation of the lattice constant from Vegard's law was observed for CdSe1−x Sx alloys at different concentrations but a little larger deviation of the bulk modulus from linear concentration dependence (LCD) was observed for considered alloy with downward bowing. We have also explored the effect of Sulfur composition on electronic properties using LDA and LDA+U. It was observed that by applying LDA+U method band gap for CdSe1−x Sx enhanced to experimental value. Elastic constants such as C11, C12, C44, Young Modulus, and Shear Modulus are also calculated and it is observed that CdSe1−x Sx compound is ductile in nature.